2020
DOI: 10.1002/jso.26354
|View full text |Cite
|
Sign up to set email alerts
|

Use of tranexamic acid is not associated with complications following bipolar hemiarthroplasty for metastatic disease

Abstract: Introduction Advances in the care of cancer patients have resulted in increased survival. The proximal femur is a common site for metastatic disease, often requiring surgical intervention. Tranexamic acid (TXA) has proven to be safe in elective and traumatic femoral hemiarthroplasty; however, its use has not been investigated in oncologic patients. Method We reviewed 66 patients (37 males) with a mean age of 64 ± 3 years undergoing a hemiarthroplasty for metastatic disease in the femoral neck. A total of 22 (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…The intraoperative use of TXA was not associated with a greater incidence of thromboembolic events, which is in line with the findings of a number of recent investigations and may justify the continued adoption of this drug in the musculoskeletal oncology population [5][6][7] . However, TXA did not reduce the rate of reoperation for irrigation and debridement, and therefore may not entirely mitigate postoperative hematoma and subsequent infection.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The intraoperative use of TXA was not associated with a greater incidence of thromboembolic events, which is in line with the findings of a number of recent investigations and may justify the continued adoption of this drug in the musculoskeletal oncology population [5][6][7] . However, TXA did not reduce the rate of reoperation for irrigation and debridement, and therefore may not entirely mitigate postoperative hematoma and subsequent infection.…”
Section: Discussionsupporting
confidence: 87%
“…oncology population, and with some reservation [5][6][7] . Although the hypercoagulability of patients with tumors may justify this reservation, TXA may reduce the need for blood transfusions and, potentially, the postoperative formation of hematoma substantially enough to prevent a return to the operating room 6,7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Haase et al 61 for example, found that topical TXA can reduce perioperative blood loss, transfusion rates, hospitalization, and VTE occurrence. Differently, Owen et al 62 did not show a reduction in blood loss and in blood transfusions when intravenous TXA was administrated before bipolar hemiarthroplasty for metastatic disease and at the time of closure. However, this study was conducted on a small and heterogeneous cohort of patients.…”
Section: Orthopedic Surgerymentioning
confidence: 87%
“…Differently, Owen et al 62 did not show a reduction in blood loss and in blood transfusions when intravenous TXA was administrated before bipolar hemiarthroplasty for metastatic disease and at the time of closure. However, this study was conducted on a small and heterogeneous cohort of patients.…”
Section: Clinical Usage and Efficacy Of Tranexamic Acid In Oncologic ...mentioning
confidence: 87%